2016
DOI: 10.1016/j.expneurol.2015.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous neurogenic cell response in the mature mammalian brain following traumatic injury

Abstract: In the mature mammalian brain, new neurons are generated throughout life in the neurogenic regions of the subventricular zone (SVZ) and the dentate gyrus (DG) of the hippocampus. Over the past two decades, extensive studies have examined the extent of adult neurogenesis in the SVZ and DG, the role of the adult generated new neurons in normal brain function and the underlying mechanisms regulating the process of adult neurogenesis. The extent and the function of adult neurogenesis under neuropathological condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 115 publications
2
51
0
Order By: Relevance
“…The finding of an early increase in neurogenesis after an FPI is consistent with findings from several different models of TBI, 12,[24][25][26] and the observation of hilar ectopic cells within a week of an FPI in mice is novel.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The finding of an early increase in neurogenesis after an FPI is consistent with findings from several different models of TBI, 12,[24][25][26] and the observation of hilar ectopic cells within a week of an FPI in mice is novel.…”
Section: Discussionsupporting
confidence: 76%
“…12,[24][25][26] Notably, the severity and/or type of injury was found to impact differential changes in hippocampal neurogenesis, 12 and altered neurogenesis was found to be associated with cognitive impairment. [27][28][29] Interestingly, Robinson et al 11 used the same model as in the current study and found no significant differences in the DCX-labeled cells in the dentate gyrus at 30 d after an FPI.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of adult neurogenesis has captivated researchers and the public alike -not only because its acceptance overturned long-held and deeply rooted dogma in our understanding of the brain [Altman and Das, 1965;Goldman and Nottebohm, 1983], but also because of the potential it holds for advancing therapeutic interventions for neurodegenerative diseases and traumatic brain injury [Hallbergson et al, 2003;Galvan and Bredesen, 2007;Brainard and Doupe, 2013;Sun, 2016]. However, there are many perplexing aspects of adult neurogenesis for which we have yet to find satisfactory explanations.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors such as exercise, enriched environment, or stress can also affect the level of neurogenesis (Gould et al, 1997, Kempermann et al, 1997, van et al, 1999 and Kempermann et al, 2000). Studies have shown that TBI induces an up-regulation of neurogenesis in varying types of TBI models as described in a previous review (Sun 2015). The injury-induced adult born neurons are also capable of functional integration into the hippocampal network (Villasana et al, 2015) and are directly associated with spontaneous cognitive functional recovery observed following injury (Sun et al, 2007; Sun et al, 2015; Blass et al 2013).…”
Section: Introductionmentioning
confidence: 89%
“…The injury-induced adult born neurons are also capable of functional integration into the hippocampal network (Villasana et al, 2015) and are directly associated with spontaneous cognitive functional recovery observed following injury (Sun et al, 2007; Sun et al, 2015; Blass et al 2013). Thus far, strategies such as supplementing varying types of growth factors, manipulating transcriptional regulators, or other pharmacological approaches targeting different aspects of the endogenous neurogenic response have shown promising results improving functional recovery following TBI as summarized in a recent review (Sun 2015). These studies clearly demonstrate that manipulation of this endogenous cell response holds potential for therapeutic advances in TBI treatments.…”
Section: Introductionmentioning
confidence: 99%